2002
DOI: 10.1023/a:1020304212118
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In the southern part of Korup National Park, Cameroon, the mast fruiting tree Microberlinia bisulcata occurs as a codominant in groves of ectomycorrhizal Caesalpiniaceae within a mosaic of otherwise species-rich lowland rain forest. To estimate the amount of carbon and nutrients invested in reproduction during a mast fruiting event, and the consequential seed and seedling survival, three related field studies were made in 1995. These provided a complete seed and seedling budget for the cohort. Seed production … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…While it is hypothesized that masting could provide an evolutionary advantage through predator satiation and dispersal efficiency (Kelly & Sork, 2002), high seedling mortality is usually recorded shortly after germination, limiting recruitment (Abrams & Johnson, 2013;Green & Newbery, 2002). For both masting and nonmasting species, factors that determine recruitment can be complex, species-specific, and change along both temporal and spatial axes (Fricke, Tewksbury, & Rogers, 2014;Oshima et al, 2015;Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is hypothesized that masting could provide an evolutionary advantage through predator satiation and dispersal efficiency (Kelly & Sork, 2002), high seedling mortality is usually recorded shortly after germination, limiting recruitment (Abrams & Johnson, 2013;Green & Newbery, 2002). For both masting and nonmasting species, factors that determine recruitment can be complex, species-specific, and change along both temporal and spatial axes (Fricke, Tewksbury, & Rogers, 2014;Oshima et al, 2015;Zhu et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Another topographical site characteristic, aspect, has been shown to influence plant association (Badano, Cavieres, Molina-Montenegro, & Quiroz, 2005;Warren, 2008), but not adult tree survival or mortality (Wu, Franklin, Liu, & Lu, 2017). Recruitment following a masting event is commonly assessed as a percentage of seedlings that survive at a given point in time (for example, Frey et al, 2007;Green & Newbery, 2002). Studies that assess several predictors-both abiotic and biotic-to explain what is driving survival of a masting species along a temporal axis are rare (but see Cleavitt et al, 2014;Norghauer & Newbery, 2016;Oshima et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For every tree ≥ 10 cm DBH (diameter at breast height; these measured last in 2005; Newbery et al 2013), the crown edges were measured along six bearings (60° increments) to the nearest 0.5 m, aided by a right-angle prism. Then, four 1-m radius circular ground plots (each 3.14 m 2 in area) were set up midway along the tree crown extensions on the four cardinal bearings (N, E, S, W), this positioning preventing sampling pod valves possibly originating from a large neighbouring conspecific fruiter (an issue that arose in Green and Newbery 2002). In each plot, all found pod valves were counted (two valves = one pod), as well as their respective seed scars (Supplementary material 1).…”
Section: Tree-level Fecundity Measurementsmentioning
confidence: 99%
“…In subtropical South America, drought increased seed production of Araucaria angustifolia [39]. A study of masting in Microberlinia bisulcata in Cameroon rainforests showed a response of seed crops after drought [38]. Drought was shown to trigger mass reproduction of Shorea forests in Malaysia [49].…”
Section: (B) Indirect Interactionsmentioning
confidence: 99%